Gaya Bicara dan Pemilihan Kata dalam Dakwah Ustadzah Halimah Alaydrus pada Vlog Berjudul "Dunia Masih Indah Selama Ada Rasulullah” - Maharani, Anisa Nur; Hindun, Hindun; Putri, Siva Risthavania; Hasanah, Yulia Nur (Aksara: Jurnal Bahasa dan Sastra, 2025)
A person's speaking style is a manifestation of various individual characteristics that influence the way they convey messages and influence their listeners. This research method is descriptive qualitative. The data source for this research is Ustadzah Halimah Alaydrus's Da'wah Vlog entitled "The World is Still Beautiful as Long as There is a Rasulullah". Data collection techniques in this research used listening and note-taking techniques. This research aims to explore various aspects of Ustazah Halimah Alaydrus' speech style and language style in the context of argument formation, emotional expression, and influence on public opinion on the YouTube platform. The primary focus is to understand how these rhetorical elements play a role in conveying important messages effectively.Keywords: Rhetoric, Style of Speech, Style of Language